FAILURES IN THE GOVERNANCE OF COASTAL AUTHORITY IN THE DESIGNATION OF NATIONAL STRATEGIC PROJECTS: A CASE STUDY OF REMPANG ECO CITY FROM THE PERSPECTIVE OF LAW NO. 23 OF 2014 ON LOCAL GOVERNMENT - Fitriana Fitriana; Yustina Yustina (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2026)
This study aims to analyze governance failure in the designation of the Rempang Eco City National Strategic Project (PSN) from the perspective of Law Number 23 of 2014 on Regional Government. The central problem lies in whether the PSN designation through Ministerial Coordination Regulation No. 7 of 2023 violated provincial coastal authority as mandated under Article 27 of Law No. 23 of 2014. Drawing on the theories of decentralization, intergovernmental relations, and administrative law, this study employs a qualitative-descriptive approach using a single case study method and document analysis. The findings reveal three administrative defects: (1) overlapping authority between the central and provincial governments in coastal zoning; (2) the absence of the Riau Islands Province Coastal and Small Island Zoning Plan (RZWP-3K) as an investment prerequisite; and (3) the lack of vertical intergovernmental coordination mechanisms consistent with decentralization principles. The revocation of PSN status through Presidential Regulation No. 12 of 2025 confirms this policy failure, yet lacks adequate administrative transition mechanisms. This study recommends reforming PSN designation procedures to mandate fulfillment of provincial coastal spatial planning prerequisites and institutionalizing vertical coordination mechanisms in small island governance.